Early childhood obesity: a survey of knowledge and practices of physicians from the Middle East and North Africa - Inge Gies; Bader AlSaleem; Beheshteh Olang; Berkouk Karima; Gamal Samy; Khaled Husain; Mahmoud Elhalik; Mohamad Miqdady; Mohamad Rawashdeh; Mohamed Salah; Nezha Mouane; Pejman Rohani; et al. (BMC, 2017)
Abstract Background Childhood obesity is one of the most serious public health issues of the twenty-first century affecting even low- and middle-income countries. Overweight and obese children are more likely to stay obese into adulthood. Due to the paucity of data on local practices, our study aimed to assess the knowledge and practices of physicians from the Middle East and North Africa region with respect to early-onset obesity. Methods A specific questionnaire investigating the perception and knowledge on early-onset obesity was circulated to healthcare providers (general physicians, pediatricians, pediatric gastroenterologist, neonatologists) practicing in 17 Middle East and North African countries. Results A total of 999/1051 completed forms (95% response) were evaluated. Of all respondents, 28.9% did not consistently use growth charts to monitor growth during every visit and only 25.2% and 46.6% of respondents were aware of the correct cut-off criterion for overweight and obesity, respectively. Of those surveyed, 22.3, 14.0, 36.1, 48.2, and 49.1% of respondents did not consider hypertension, type 2 diabetes, coronary heart disease, fatty liver disease, and decreased life span, respectively, to be a long-term complication of early childhood obesity. Furthermore, only 0.7% of respondents correctly answered all survey questions pertaining to knowledge of early childhood overweight and obesity. Conclusion The survey highlights the low use of growth charts in the evaluation of early childhood growth in Middle East and North Africa region, and demonstrated poor knowledge of healthcare providers on the short- and long-term complications of early-onset obesity. This suggests a need for both continued professional education and development, and implementation of guidelines for the prevention and management of early childhood overweight and obesity.